2009
DOI: 10.1124/jpet.108.150029
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Esterase Prevents Cocaine-Induced Toxicity and the Ongoing Intravenous Self-Administration of Cocaine in Rats

Abstract: Cocaine esterase (CocE) is a naturally occurring bacterial enzyme, is a very efficient protein catalyst for the hydrolysis of cocaine, and has previously been shown to protect rodents from the lethal effects of cocaine. The current studies were aimed at evaluating the capacity of a longer acting mutant form (CocE T172R/G173Q; DM CocE) of CocE to protect against the lethal effects of cocaine, and alter ongoing intravenous cocaine self-administration in rats. A dose-response analysis revealed a dose-dependent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 24 publications
(47 reference statements)
3
64
0
2
Order By: Relevance
“…Previous studies with mutant bacterial CocEs (Brim et al, 2010;Collins et al, 2009) or mutant human BChEs (Carroll et al, 2011) have demonstrated the capacity of highly efficient cocaine-specific hydrolase to inhibit the reinforcing effects of cocaine; however, in each of these studies the inhibitory effects of the enzymes were short-lived, lasting from minutes to hours. The results of the current studies with PEG-CCRQ CocE not only confirm this effect of cocaine-specific esterases, but they also provide convergent evidence that PEG-CCRQ CocE represents a significant improvement over previously described mutant bacterial and human cocaine hydrolases with respect to both the magnitude and duration of its antagonism of the reinforcing effects of cocaine.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Previous studies with mutant bacterial CocEs (Brim et al, 2010;Collins et al, 2009) or mutant human BChEs (Carroll et al, 2011) have demonstrated the capacity of highly efficient cocaine-specific hydrolase to inhibit the reinforcing effects of cocaine; however, in each of these studies the inhibitory effects of the enzymes were short-lived, lasting from minutes to hours. The results of the current studies with PEG-CCRQ CocE not only confirm this effect of cocaine-specific esterases, but they also provide convergent evidence that PEG-CCRQ CocE represents a significant improvement over previously described mutant bacterial and human cocaine hydrolases with respect to both the magnitude and duration of its antagonism of the reinforcing effects of cocaine.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, just as the prolonged duration of PEG-CCRQ CocE's protective effects differentiated it from DM CocE in rodent models of acute cocaine toxicity (Collins et al, 2011b;Narasimhan et al, 2011) differences between these enzymes began to emerge when PEG-CCRQ CocE was evaluated against cocaine self-administration using a multiple dose procedure that allowed for the longitudinal evaluation of an animal's sensitivity to the reinforcing effects of cocaine. Unlike the effects of B3 mg/ kg DM CocE, which had completely dissipated by 24 h (Collins et al, 2009), pretreatment with 3.2 mg/kg PEG-CCRQ CocE produced a longer lasting change in cocaine self-administration with a three-fold rightward shift in the dose-response curve observed 24 h later, and baseline-like rates of responding not observed until 48 h after administration. Interestingly, in addition to producing larger Figure 7 Effects of 32.0 mg/kg; IV PEG-CCRQ CocE on the cocaine-like interoceptive effects of methylphenidate, d-amphetamine, and cocaine.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations